Odonata Ordo Biodiversity Index at The Lake I Nyoman Sukadana PT Kilang Pertamina Internasional Refinery Unit VII Kasim - Yusuf, Muhammad; Ferdy Saputra; Bambang Imawan (Prospect Publishing, 2024)
I Nyoman Sukadana lake was located on buffer zone area at PT Kilang Pertamina Internasional Refinery Unit VII Kasim. This area was plotted as conservation area for any kind of flora, fauna, and company’s springs. I Nyoman Sukadana become a habitat for several kinds of bird and insect. Dragonfly which has dominant life cycle at the waters become one of several insects that could be found on this area. This research calculates biodiversity index of dragonfly at I Nyoman Sukadana Lake’s area. It calculates biodiversity index (H’), evenness (E), and richness (R). Data retrieval conducted by line transect method and Shannon-Wiener index for data analysis. This research found that there are 23 kinds of dragonfly on I Nyoman Sukadana Lake which dominated by Sub-Ordi Anisoptera. This sub-ordo was living on open waters area, so I Nyoman Sukadana Lakes was a suitable habitat for Sub-Ordi Anisoptera. Based on biodiversity index (H’) calculation it’s got 2,02 that categorized as “High”, evenness (E) at 0,87, and richness index (R) at 5,13 that categorized as “High”. Based on Shannon-Wiener index, it’s indicating that the water quality of I Nyoman Sukadana Lake was fine.